Detection of Submeter Scale Irregularities in the Low‐Latitude Ionospheric E Layer Using High VHF Radar at 205 MHz. Issue 5 (25th May 2019) - V., Rakesh; Manoj, M. G.; Mohankumar, K.; Neethu, M.; Samson, Titu K.
Abstract: A preliminary study on the first‐time observation of the submeter‐scale disturbances in the ionospheric E layer above the near‐equatorial site of Cochin (10.04°N, 76.33°E; Declination: −1°37′, Inclination: 7°2′), India, using an atmospheric radar in the high very high frequency range at 205 MHz has been carried out. Selected cases of E layer disturbances observed in the 90‐ to 105‐km altitude region, during summer, equinox, and winter periods are reported. It is noted that the submeter‐scale disturbances exist in the near‐equatorial E region with a life span of few minutes to several hours. Both continuous and intermittent echoes were seen in the 90‐ to 105‐km region. The continuous irregularities remain at constant altitude initially, descend and vanish in the later stage. The E layer irregularities observed in the morning and noon were continuous, whereas the echoes after the late afternoon were quasiperiodic in nature with a lifetime of 10–15 min. However, no apparent mean Doppler is observed during this period and is expected to be associated with a turbulent cascade from long wavelengths to shorter ones. Key Points: First‐time detected E layer echoes by 205 MHz stratosphere‐troposphereradar Presence of E layer echoes for a few minutes to several hours is noted Echoes remain at constant altitude initially and then descend